1997
DOI: 10.1007/s004140050094
|View full text |Cite
|
Sign up to set email alerts
|

Additional primer sets for an amelogenin gene PCR-based DNA-sex test

Abstract: When aligning the human amelogenin X (AmelX)-gene with the human amelogenin Y (AmelY)-gene, 19 regions of absolute homology ranging in size from 22 to 80 bp, 5 deletions located on AmelX from 1 to 6 bp and 5 deletions 1-183 bp long located on AmelY can be observed. The regions of absolute homology are used to design primer sets which span deletions of the X- and/or Y-chromosome. The PCR products generated on the X- and Y-homologues differ in size. New regions of deletions and newly designed primers are describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 15 publications
0
31
0
1
Order By: Relevance
“…The amelogenin gene present on the X (AMEL X) and the Y (AMEL Y) chromosomes of humans (Bailey et al 1992) showed size differences between these two chromosomes and therefore, this gene has been used to differentiate males from females (Mannucci et al 1994;Haas-Rochholz and Weiler 1997). Various companies manufacture multiplex STR kits containing the amelogenin system for individual and gender identification, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The amelogenin gene present on the X (AMEL X) and the Y (AMEL Y) chromosomes of humans (Bailey et al 1992) showed size differences between these two chromosomes and therefore, this gene has been used to differentiate males from females (Mannucci et al 1994;Haas-Rochholz and Weiler 1997). Various companies manufacture multiplex STR kits containing the amelogenin system for individual and gender identification, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Several PCR primer sets have been developed [3,4,5,6,7,8], and the most commonly used PCR-based sex test is the one described by Sullivan et al [6], flanking a 6bp deletion on the X homologue, resulting in 106 bp and 112 bp PCR products from the X and Y chromosomes, respectively. Amelogenin-based sex tests are part of various PCR multiplex reaction kits from different manufacturers which are widely used for DNA typing of both reference samples and casework samples in the forensic field [ [14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Further examinations were performed with three alternate single AMEL primer pairs [2,15] (Fig. 1; Table 1).…”
Section: Samplesmentioning
confidence: 99%